MEKANISME VERIFIKASI SUARA PENDUKUNG CALON KEPALA DAERAH PERSEORANGAN DALAM UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PEMILIHAN KEPALA DAERAH - M. Saada Hilman; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a constitutional state as stated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. The concept of a rule of law cannot be separated from the concept called democracy. One of the parameters for the development of democracy and people's sovereignty in Indonesia is reflected in the General Election. It is stated in Article 28D paragraph (3) of the 1945 Constitution which states that, "every citizen has the right to get equal opportunities in government". In its development, participants in the regional head election are not only followed by candidates from political parties or coalitions of political parties, but also from independent or individual candidates. Through the Decision of the Constitutional Court Number 5 / PUU-V / 2007, the Constitutional Court decided it was open to individual or independent candidates. In addition, the implementation also adopts the concept of administrative verification and factual verification. As for the purposes of writing this thesis, namely: First, to determine the relevance of the factual verification process carried out within 14 (fourteen) days, Second, to find out the verification mechanism in accordance with the number of requirements and the census method.This type of research is normative juridical research, which is research that is carried out by examining secondary legal materials or research based on standardized rules that have been recorded and discussing legal principles and legal synchronization. Sources of data used in this study are primary data, secondary data and tertiary data.From the results of this study, it can be concluded that the 14 (fourteen) days period is very irrelevant because the number of supporting requirements that have been verified is very large, the minimum number of PPS officers assigned, limited implementation time, areas that are difficult to access and supporters that cannot be found. The verification mechanism in accordance with this is as stipulated in law but with efficient terms and time in its implementation.Keywords: Verification - Regional Head Election - Individual Candidates